Commentary on the Anti-Fascism, White Supremacy, and the “New” Right Teach-In - O'Connell, Anne; Badwall, Harjeet; Macias, Teresa; Rwigema, MJ; Polar, Brenda; Rahmani, Ashkan; Ramos, Pablo (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2019)
A commentary on, and pedagogical materials of, York University School of Social Work's Social Action for Social Change Committee's week-long Teach-In on the rise of fascism, white supremacy, and the “new” right, across Canada and internationally.